Role of Intravenous Magnesium Sulphate in Term Neonates with Severe Birth Asphyxia in Terms of Immediate Neurological Outcome - Ahmed, Aamina; Jabeen, Aqeela; Sattar, Hina; Bibi, Zainab (Indus Journal of Bioscience Research, 2025)
Introduction: Different treatment modalities are used worldwide for birth asphyxia, including initiation of therapeutic hypothermia within 3 hours after birth. Some modalities under research are intravenous magnesium sulphate, endogenous cannabinoids, stem cell therapy, xenon, argon, allopurinol, and topiramate. Objectives: To determine frequency of neurological outcome and mortality of term neonates with severe birth asphyxia treated with and without intravenous magnesium sulphate (MgSO4). Methodology: A total of 102 neonates were randomized equally to treatment and placebo groups (group A and B). Sampling technique used was non-probability consecutive sampling using simple randomization. Group A got two additional doses of magnesium sulfate at 24 and 48 hours after receiving an infusion of 250 mg/kg/dose in 10% dextrose to make volume equal to 3.0 mL/kg/dose over the course of an hour, after first dose at admission. 10% dextrose 3.0 mL/kg/dose was given to the control group over the course of an hour, with two further doses given at comparable intervals. Outcome was noted in both groups in terms of improvement in neurological findings and death of neonate during hospital admission. Results: Neurological improvement in terms of improvement in establishment of feed were recorded in 42 (82.35%) of the patients in group A and 33 (64.71%) of the patients in group B (p-value = 0.043). Additionally, death was documented in 04 (7.84%) and 12 (23.53%) patients, respectively (p-value = 0.029). Conclusion: The study indicated that magnesium sulfate had the potential to be used as a neuroprotective intervention in neonatal care since it greatly improved the appearance of a good sucking reflex in neonates with severe birth asphyxia.